CALCULATING THE CONTRIBUTION OF ZOOXANTHELLAE TO GIANT CLAMS RESPIRATION ENERGY REQUIREMENTS - Ambariyanto (JOURNAL OF COASTAL DEVELOPMENT, 2002)
Giant clams (Tridacnidae) are known to live in association with photosynthetic single cell dinoflagellate algae commonly called zooxanthellae. These algae which can be found in the mantle of the clams are capable of transferring part of their photosynthates which become an important source of energy to the host ( apart from filter feeding activity). In order to understand the basic biological processes of the giant clams , the contribution of zooxanthellae to the clam’s energy requirement need to be determined. This review describes how to calculate the contribution of zooxanthellae to the giant clam’s energy requirement for the respiration process.